2013
DOI: 10.1111/aor.12233
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Microbial Growth on Chitosan Membranes by Plasma Treatment

Abstract: The use of polymeric medical devices has stimulated the development of new sterilization methods. The traditional techniques rely on ethylene oxide, but there are many questions concerning the carcinogenic properties of the ethylene oxide residues adsorbed on the materials after processing. Another common technique is the gamma irradiation process, but it is costly, its safe operation requires an isolated site, and it also affects the bulk properties of the polymers. The use of gas plasma is an elegant alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Plasma surface modification results in enhanced endothelial cell adhesion 47 and improved antimicrobial efficiency. 48 Hence, plasma-modified PU-VCO scaffold may provide a suitable environment for endothelial cell adhesion resulting in improved properties facilitating the vascular tissue growth. Recently, Wu et al 49 reported that the ideal cardiovascular patch material should possess long durability, resistance to degradation and infection, and non-toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma surface modification results in enhanced endothelial cell adhesion 47 and improved antimicrobial efficiency. 48 Hence, plasma-modified PU-VCO scaffold may provide a suitable environment for endothelial cell adhesion resulting in improved properties facilitating the vascular tissue growth. Recently, Wu et al 49 reported that the ideal cardiovascular patch material should possess long durability, resistance to degradation and infection, and non-toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4,13 ] Conventional sterilization methods including dry or wet heat, radiation, and chemical sterilant cause alterations in chitosan's properties and may leave toxic residues. [ 14–29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have been published on surface modifications of chitosan membranes caused by plasma interactions. [ 17,31–33 ] The reports examine changes in physicochemical properties, biological properties, and antimicrobial properties of the chitosan membranes. These reports do not examine depyrogenation of chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…A powder form of CS was also desired to enhance the effectiveness of a novel sterilization method for CS based on non-thermal nitrogen gas plasma (NtNP) (de Oliveira Cardoso Macedo, de Macedo, Gomes, de Freitas Daudt, Rocha & Alves, 2013). Plasma is considered the fourth state of matter and consists of an ionized gas that has emergent properties the gas alone does not, such as magnetism and conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma is considered the fourth state of matter and consists of an ionized gas that has emergent properties the gas alone does not, such as magnetism and conductivity. Use of NtNP for sterilization of CS is necessitated by the fact that conventional sterilization methods like dry/wet heat, radiation, and chemical sterilants cause caramelization of the polysaccharide, chain scissions, and/or may leave residual toxic residues in the material (de Oliveira Cardoso Macedo, de Macedo, Gomes, de Freitas Daudt, Rocha & Alves, 2013; Franca et al, 2013; Lim, Khor & Koo, 1998; Lim, Khor & Ling, 1999; Marreco, da Luz Moreira, Genari & Moraes, 2004; Norzita, Norhashidah, Maznah, Nurul Aizam Idayu Mat, Nor Akma & Norafifah Ahmad, 2013; Rao & Sharma, 1995; Rosiak, Ulański, Kucharska, Dutkiewicz & Judkiewicz, 1992; San Juan et al, 2012). These physicochemical changes result in changes in the biological properties of CS making these methods non-optimal for sterilizing CS.…”
Section: Introductionmentioning
confidence: 99%